MALT1 cleaves the E3 ubiquitin ligase HOIL‐1 in activated T cells, generating a dominant negative inhibitor of LUBAC‐induced NF‐κB signaling. (26th November 2015) - Elton, Lynn; Carpentier, Isabelle; Staal, Jens; Driege, Yasmine; Haegman, Mira; Beyaert, Rudi
Abstract : Human paracaspase 1 (PCASP1), better known as mucosa associated lymphoid tissue lymphoma translocation 1 (MALT1), plays a key role in immunity and inflammation by regulating gene expression in lymphocytes and other immune cell types. Deregulated MALT1 activity has been implicated in autoimmunity, immunodeficiency and certain types of lymphoma. As a scaffold MALT1 assembles downstream signaling proteins for nuclear factor‐κB (NF‐κB) activation, while its proteolytic activity further enhances NF‐κB activation by cleaving NF‐κB inhibitory proteins. MALT1 also processes and inactivates a number of mRNA destabilizing proteins, which further fine‐tunes gene expression. MALT1 protease inhibitors are currently developed for therapeutic targeting. Here we show that T cell activation, as well as overexpression of the oncogenic fusion protein API2–MALT1, induces the MALT1‐mediated cleavage of haem‐oxidized IRP2 ubiquitin ligase 1 (HOIL‐1). In addition, to acting as a K48‐polyubiquitin specific E3 ubiquitin ligase for different substrates, HOIL‐1 co‐operates in a catalytic‐independent manner with the E3 ubiquitin ligase HOIL‐1L interacting protein (HOIP) as part of the linear ubiquitin chain assembly complex (LUBAC). Intriguingly, cleavage of HOIL‐1 does not directly abolish its ability to support HOIP‐induced NF‐κB signaling, which is still mediated by the N‐terminal cleavage fragment, but generates a C‐terminal fragment with LUBAC inhibitory properties. We propose that MALT1‐mediated HOIL‐1 cleavage provides a gain‐of‐function mechanism that is involved in the negative feedback regulation of NF‐κB signaling. Abstract : Human paracaspase 1, better known as MALT1, has a key role in immunity and inflammation. MALT1 is activated in response to T‐cell receptor stimulation and many other triggers, and its proteolytic activity has emerged as a therapeutic target for cancer and autoimmune diseases. MALT1 acts as a scaffold for downstream signaling proteins to activate HOIP/HOIL‐1 (the linear ubiquitin chain assembly complex, LUBAC) dependent NF‐κB signaling. Here Beyaert and colleagues show that MALT1 proteolytic activity cleaves HOIL‐1, generating a C‐terminal fragment that inhibits LUBAC‐induced NF‐κB signaling as part of a negative feedback mechanism.